Agatha Christie - Wagoner, Mary. (Boston : Twayne Publishers, 1986)
A critical study of the author and her work integrating biographical information into criticism.
Includes bibliographical references (p. 151-157) and index.
Booklist.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Christie, Agatha, -- 1890-1976 -- Criticism and interpretation; Christie, Agatha, -- 1890-1976.; Detective and mystery stories, English -- History and criticism; Mystery fiction -- History and criticism